2002
DOI: 10.1542/peds.110.1.e5
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Metabolism in Children and Adolescents With Moderate to Severe Cerebral Palsy

Abstract: ABSTRACT. Objectives. Diminished bone density and a propensity to fracture with minimal trauma are common in children and adolescents with moderate to severe cerebral palsy (CP). The purpose of this study was to provide a detailed evaluation of bone mineral density (BMD) and metabolism in this population and to assess the relationship of these measures to multiple other clinical, growth, and nutrition variables.Methods. The study group consisted of 117 subjects ages 2 to 19 years (mean: 9.7 years) with moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
333
5
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(360 citation statements)
references
References 47 publications
13
333
5
9
Order By: Relevance
“…In a population-based setting, Leet et al [9] investigated fracture histories obtained from medical charts of 763 CP patients (aged between 1.3 and 18 years), and found that 70% of fractures involved the lower extremities. These results are consistent with the finding that bone mineral density (BMD) in the femur is severely diminished in children with moderate to severe CP [3]. Shiragaki et al [17] also showed that BMD in the lower limbs was lower than other bone sites in …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a population-based setting, Leet et al [9] investigated fracture histories obtained from medical charts of 763 CP patients (aged between 1.3 and 18 years), and found that 70% of fractures involved the lower extremities. These results are consistent with the finding that bone mineral density (BMD) in the femur is severely diminished in children with moderate to severe CP [3]. Shiragaki et al [17] also showed that BMD in the lower limbs was lower than other bone sites in …”
Section: Discussionsupporting
confidence: 90%
“…Increased risk of fracture in physically disabled children may be associated with their low bone mass. We did not assess bone mass of the subjects, but other researchers have shown that lower bone mass has been reported in children with CP [3,4]. Likewise, low vitamin D status, which could adversely affect normal bone metabolism, has been reported in children with neuromuscular disorders [5,14], and thus may also be associated with increased risk of fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral distal femoral DXA scan reflects BMD in the legs, the regions most likely to incur fractures. Fractures in this population differed from fractures seen in other neuromuscular disorders such as cerebral palsy [4]; the nature of the radiographic changes suggested subperiosteal hemorrhage and Charcot-like changes in the physis, which might be attributed to chronic repetitive trauma and could not properly be described as an ''insufficiency fracture.'' According to the ISCD, only children who have experienced an insufficiency fracture (a fracture occurring with minimal trauma) should be diagnosed with ''osteoporosis.''…”
Section: Discussionmentioning
confidence: 55%
“…In cerebral palsy (CP) patients with motor deficiencies the examination of biochemical bone markers (OC, B-ALP, and N-telopeptides) have shown a wide variety in serum levels (30,31) and no significant association with measures of bone mass as BMD z scores of the lumbar spine (30,31) and distal femur region (31). Furthermore, a study comparing children with CP and healthy children reported no significant differences in both bone formation (B-ALP) and (urinary) resorption markers (32).…”
Section: Rett Syndrome and Low Bone Turnovermentioning
confidence: 99%